Beyond GDP: The Quest for a Measure of Social Welfare - Fleurbaey, Marc (Journal of Economic Literature, 2009)
This paper critically examines the various approaches to the measurement of individual well-being and social welfare that have been considered for the construction of alternatives to GDP. Special attention is devoted to recent developments in the analysis of sustainability, in the study of happiness, in the theory of social choice and fair allocation, and in the capability approach. It is suggested in the conclusion that, although convergence toward a consensual approach is not impossible, for the moment not one but three alternatives to GDP are worth developing. (JEL I31, E23, E01)